STRENGTHENING YOUTH FINANCIAL CAPABILITY: A COMMUNITY APPROACH IN MOYUDAN’S DIGITAL FINANCE LANDSCAPE - Khusniati, Navi'ah; Oktabriyantina , Wulan; Sanjoko, Deny Cahyadinanto; Yusuf, Maulana Ghani Yusuf (Kirana Publisher, 2025)
On the technological advances and shifting global economic trends oblige today’s youth, particularly young women, to master sound financial principles that discourage excessive spending and safeguard them from hazards in the digital finance realm. A community-based training program was carried out for Nasyiatul ʿAisyiyah (NA) Moyudan members to address this need. Designed collaboratively and delivered in an interactive format, the workshops explored budgeting, saving, investing, financial protection, and online security. Program impact was measured with a paired-samples t-test comparing the pre- and post-training scores of 24 participants. Results revealed an average gain of 23.75 points (p < 0.001), demonstrating a marked increase in financial understanding following the sessions. The evidence indicates that context-specific, participatory financial-literacy instruction can meaningfully strengthen young women’s financial competence and is a preventive step toward bolstering the economic resilience of the upcoming generation.